Preparation method of degradable intelligent food packaging film

By blending PVA and CS and adding ingredients such as curcumin and CUR, a degradable smart food packaging film was prepared, which solved the shortcomings of the existing films in terms of mechanical properties and barrier properties, and realized the monitoring of food freshness, effectively protecting food and reducing health risks.

CN119823427APending Publication Date: 2025-04-15XIAMEN UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510049925.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing biodegradable food packaging films have shortcomings in terms of mechanical properties and barrier properties, which cannot effectively protect food, and lack the ability to monitor food quality and safety.

Method used

A degradable smart food packaging film was prepared by solution casting using polyvinyl alcohol (PVA) and chitosan (CS) as the matrix. This film not only improves mechanical properties and water resistance, but also has the function of monitoring food freshness.

Benefits of technology

The film has been improved with improved mechanical properties and water resistance, which can effectively protect food, and monitor the freshness of food through color changes, reducing health problems caused by accidental consumption of spoiled food.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823427A_ABST
    Figure CN119823427A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a degradable intelligent food packaging film, and belongs to the field of packaging films. The preparation method comprises the following steps: preparing chitosan (CS), polyvinyl alcohol (PVA), curcumin (CUR), glacial acetic acid, glycerol and other raw materials; the method comprises the following steps: firstly, dissolving CS powder in glacial acetic acid, and completely dissolving CS under continuous heating and stirring; and adding PVA into the deionized water, heating and stirring until PVA is completely dissolved. Then mixing the two solutions according to different volume ratios, adding glycerol and CUR, continuously stirring in a water bath environment, then naturally cooling to room temperature, and standing; and finally, casting the mixed solution in a culture dish, and drying in a drying oven to form the film. The food-grade degradable intelligent packaging material is successfully developed by taking CS and PVA as matrixes and adding CUR as a pH sensitive component, and the food-grade degradable intelligent packaging material has the characteristics of high safety, good water resistance, good thermal stability and degradability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of packaging films, and in particular to a method for preparing a degradable intelligent food packaging film. Background Art

[0002] Traditional plastic packaging is mostly derived from non-renewable fossil resources and is difficult to degrade in the natural environment. After being used in large quantities, these plastic wastes exist in the soil, water and other environments for a long time, causing serious damage to the ecosystem, such as soil compaction and water pollution, affecting the living environment of animals and plants and destroying the ecological balance. Plastic packaging decomposes slowly in the natural environment and may release harmful substances, such as microplastic particles. Once these microplastics enter the food chain, they may pose a potential threat to biological health, including affecting the human endocrine system and damaging organ function.

[0003] At present, with the popularization and deepening of green and sustainable development concepts, environmentally friendly biodegradable packaging has attracted people's attention. Although some degradable films have certain advantages in environmental protection, they are insufficient in mechanical properties, barrier properties, etc. For example, a single bio-based material film may not be strong enough and easily damaged during packaging, transportation and storage, and cannot effectively protect food, resulting in physical damage to the food or external contamination.

[0004] In addition, many existing food packaging films only have basic packaging functions and lack the ability to effectively monitor food quality and safety. During the food spoilage process, it is impossible to provide consumers with intuitive information in a timely manner, making it difficult for consumers to judge the freshness of food, increasing the risk of eating spoiled food. Summary of the invention

[0005] The purpose of the present invention is to solve the above problems in the prior art and provide a method for preparing a degradable intelligent food packaging film, wherein the biodegradable film is prepared using polyvinyl alcohol and chitosan as a matrix, and the food freshness monitoring capability of the packaging film is developed by introducing curcumin.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme:

[0007] A method for preparing a degradable smart food packaging film comprises the following steps:

[0008] 1) Dissolve CS in glacial acetic acid solution, heat, stir and condense under reflux to obtain a CS solution;

[0009] 2) Add PVA to deionized water, heat, stir and condense under reflux to obtain a PVA solution;

[0010] 3) mixing the CS solution and the PVA solution to obtain a mixed solution;

[0011] 4) Add glycerol and CUR to the mixture in step 3), keep stirring in a water bath, then cool naturally to room temperature and let stand to eliminate any bubbles that may exist;

[0012] 5) Cast the mixed solution in step 4) in a culture dish and place it in an oven. After the film is dry, take it out and peel it off.

[0013] In step 1), the dosage ratio of CS to glacial acetic acid solution is 10-30 g / 100 mL, the volume fraction of glacial acetic acid solution is 2%-10%, and the heating temperature is 80-100°C.

[0014] In step 2), the dosage ratio of PVA to deionized water is 10-30 g / 100 mL, and the heating temperature is 80-100° C.

[0015] In step 3), the volume ratio of the CS solution to the PVA solution is 4:1 to 2:3.

[0016] In step 4), the amount of glycerol added is 30% to 60% of the mass of the solute in the mixed solution.

[0017] In step 4), the amount of CUR added is 1% to 10% of the mass of the solute in the mixed solution.

[0018] In step 4), the water bath temperature is 50-80°C.

[0019] In step 5), the temperature of the oven is 40-70°C.

[0020] A degradable intelligent food packaging film is prepared by the above preparation method.

[0021] The application of the degradable intelligent food packaging film is used for food packaging film and monitoring the freshness of food.

[0022] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0023] The present invention blends two biodegradable materials, CS and PVA, and adds CUR as an indicator in the blending system to prepare a degradable smart food packaging film by a solution casting method. By changing the blending ratio of CS and PVA, the mechanical properties and water resistance of the film are improved, so that it can still maintain good performance under different humidity environments and effectively protect food.

[0024] The present invention adds curcumin as a pH-sensitive component, so that the film can change color according to the change of pH value during food spoilage, thereby realizing intuitive monitoring of food freshness. Consumers can timely understand the quality status of food by observing the change of film color, and reduce health problems caused by eating spoiled food by mistake. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The tensile strength test results of different samples.

[0026] Figure 2 The water resistance test results of different samples are shown in Figure 2.

[0027] Figure 3 The pH value change of fresh milk under open conditions at room temperature.

[0028] Figure 4 This is the color difference change of the composite film during the storage period of milk.

[0029] Figure 5 Color change of composite film during milk storage

[0030] Figure 6 is the correlation between the color difference ∆E of the composite film and the pH value. DETAILED DESCRIPTION

[0031] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0032] Comparative Example 1

[0033] CS was added to a 2% volume fraction glacial acetic acid solution to make the concentration of the CS solution 20% (w / v), and heated, stirred and condensed under reflux until CS was completely dissolved. The heating temperature was 80°C.

[0034] 50% of the solute mass of glycerol and 5% of CUR were added to the CS solution, and the solution was stirred continuously in a 60°C water bath until uniform, and then naturally cooled to room temperature and allowed to stand.

[0035] The mixed solution was cast in a culture dish and placed in an oven at 50°C. After the film was completely dried, it was taken out and peeled off to obtain a CS / CUR composite film.

[0036] Comparative Example 2

[0037] PVA was added to deionized water to make the concentration of the PVA solution 20% (w / v), and the solution was heated, stirred and condensed under reflux until the PVA was completely dissolved. The heating temperature was 90°C.

[0038] 50% of the solute mass of glycerol and 5% of CUR were added to the PVA solution, and the solution was stirred continuously in a 60°C water bath until uniform, and then naturally cooled to room temperature and allowed to stand.

[0039] The mixed solution was cast in a culture dish and placed in an oven at 50°C. After the film was completely dried, it was taken out and peeled off to obtain a PVA / CUR composite film.

[0040] Example 1

[0041] CS was added to a 2% volume fraction glacial acetic acid solution to make the concentration of the CS solution 20% (w / v), and heated, stirred and condensed under reflux until CS was completely dissolved. The heating temperature was 80°C.

[0042] PVA was added to deionized water to make the concentration of the PVA solution 20% (w / v), and the solution was heated, stirred and condensed under reflux until the PVA was completely dissolved. The heating temperature was 90°C.

[0043] The CS solution and the PVA solution were mixed in a volume ratio of 8:2, and 50% of the solute mass of glycerol and 5% of CUR were added to the mixture. The mixture was stirred continuously in a 60°C water bath environment until uniform, and then naturally cooled to room temperature and allowed to stand.

[0044] The mixed solution was cast in a culture dish and placed in an oven at 50°C. After the film was completely dried, it was taken out and peeled off to obtain a CS / PVA / CUR composite film.

[0045] Example 2

[0046] CS was added to a 2% volume fraction glacial acetic acid solution to make the concentration of the CS solution 20% (w / v), and heated, stirred and condensed under reflux until CS was completely dissolved. The heating temperature was 80°C.

[0047] PVA was added to deionized water to make the concentration of the PVA solution 20% (w / v), and the solution was heated, stirred and condensed under reflux until the PVA was completely dissolved. The heating temperature was 90°C.

[0048] The CS solution and the PVA solution were mixed in a volume ratio of 7:3, and 50% of the solute mass of glycerol and 5% of CUR were added to the mixture. The mixture was stirred continuously in a 60°C water bath environment until uniform, and then naturally cooled to room temperature and allowed to stand.

[0049] The mixed solution was cast in a culture dish and placed in an oven at 50°C. After the film was completely dried, it was taken out and peeled off to obtain a CS / PVA / CUR composite film.

[0050] Example 3

[0051] CS was added to a 2% volume fraction glacial acetic acid solution to make the concentration of the CS solution 20% (w / v), and heated, stirred and condensed under reflux until CS was completely dissolved. The heating temperature was 80°C.

[0052] PVA was added to deionized water to make the concentration of the PVA solution 20% (w / v), and the solution was heated, stirred and condensed under reflux until the PVA was completely dissolved. The heating temperature was 90°C.

[0053] The CS solution and the PVA solution were mixed in a volume ratio of 5:5, and 50% of the solute mass of glycerol and 5% of CUR were added to the mixture. The mixture was continuously stirred in a 60°C water bath environment until uniform, and then naturally cooled to room temperature and allowed to stand.

[0054] The mixed solution was cast in a culture dish and placed in an oven at 50°C. After the film was completely dried, it was taken out and peeled off to obtain a CS / PVA / CUR composite film.

[0055] Example 4

[0056] CS was added to a 2% volume fraction glacial acetic acid solution to make the concentration of the CS solution 20% (w / v), and heated, stirred and condensed under reflux until CS was completely dissolved. The heating temperature was 80°C.

[0057] PVA was added to deionized water to make the concentration of the PVA solution 20% (w / v), and the solution was heated, stirred and condensed under reflux until the PVA was completely dissolved. The heating temperature was 90°C.

[0058] The CS solution and the PVA solution were mixed in a volume ratio of 4:6, and 50% of the solute mass of glycerol and 5% of CUR were added to the mixture. The mixture was stirred continuously in a 60°C water bath until uniform, and then naturally cooled to room temperature and allowed to stand.

[0059] The mixed solution was cast in a culture dish and placed in an oven at 50°C. After the film was completely dried, it was taken out and peeled off to obtain a CS / PVA / CUR composite film.

[0060] The composite films prepared in Comparative Examples 1-2 (D1-D2) and Examples 1-4 (S1-S4) were tested for mechanical properties, water resistance, and milk freshness indication. The specific test methods are as follows:

[0061] (1) Mechanical properties: Tested according to GB / T 1040.3-2006, the sample was cut into 50mm pieces with a cutting knife. The initial distance between the upper and lower clamps is 50 mm, and the tensile speed is 50 mm / min. The test results are shown in Figure 1 .

[0062] (2) Water resistance: Select film samples of consistent size, place them in an oven at 50°C and dry them until the mass is constant and weigh them (recorded as M0, in g). Subsequently, immerse the sample in a petri dish containing deionized water. After 24 hours of full swelling, remove the residual moisture on the surface and weigh it again (recorded as M1, in g). Next, place the sample in an oven at 50°C again and dry it until the mass is constant, and complete the final weighing (recorded as M2, in g). Based on the above steps, the water absorption (W) of the composite material is calculated, and its solubility (S) is evaluated. The calculation formula is as follows, and the test results are shown in Figure 2 .

[0063]

[0064]

[0065] (3) Milk freshness indicator test: The composite film was immersed in 50 mL of pasteurized milk and left uncovered at room temperature of 27°C. The pH value of the pasteurized milk was measured every hour using a pH meter, and the composite film was scanned using an LS155 colorimeter. The test results are shown in Table 1. Figures 3 to 6 .

[0066] Figure 1 The tensile strength test results of the film are shown. Among them, when the mass ratio of CS to PVA is 2:8, the tensile strength of the film is the largest, which is 5.82 MPa; when the mass ratio of CS to PVA is 4:6, the tensile strength of the film is the smallest, which is 3.34 MPa. The hydrogen bonds between molecules affect the mechanical properties of the film. When CS is added, PVA and CS are physically cross-linked to form hydrogen bonds, but at the same time, the possibility of defects (such as agglomeration) in the composite film will increase.

[0067] Figure 2 The water resistance test results of the film are shown. The pure PVA film was completely dissolved during the experiment and is therefore not shown in the figure below. With the increase of PVA content, the water absorption rate increased from 5.22% to 89.83%, which may be due to the large number of hydroxyl groups in PVA forming hydrogen bonds with water molecules, resulting in an increase in water absorption. On the other hand, the solubility generally decreased with the increase of CS content. The solubility of the pure CS film and the film with a CS / PVA mass ratio of 8:2 and 7:3 was the lowest, at 38.88%, 38.05%, and 36.36%, respectively. This may be because PVA itself is rich in hydroxyl groups, making it extremely soluble in water, while CS can form hydrogen bonds with PVA to play a hydrophobic role, and the phenolic compounds in CUR interact with CS, resulting in a decrease in solubility.

[0068] Figure 3The pH value of fresh milk under open conditions at room temperature is shown. The initial pH value of fresh milk is (6.785±0.001). After 1 hour, the pH value dropped to (6.532±0.002), and the milk was still fresh and edible. After 2 hours, the pH value dropped rapidly to (5.726±0.002). This may be because a large number of bacteria have grown in the second hour. During the bacterial proliferation process, their metabolic activities decompose and consume components such as protein and lactose in the milk, and lactic acid is produced. After 3 hours, the pH value dropped to (5.036±0.003). After being stored for 4 hours, the pH value was (4.345±0.002), at which time the milk was in a spoiled state and could no longer be eaten.

[0069] Figure 4 and Figure 5 The color and color difference changes of the composite film during the milk placement period are shown. A color difference ΔE greater than 5 indicates that the color change can be detected by the human eye, and a ΔE greater than 12 means that the color has an absolute difference. Combined with the pH results, the pH value of the milk dropped slightly after 1 hour of placement. When the milk penetrated, the color of the composite film changed. The color difference data analysis showed that the overall color difference change of the film with a CS / PVA mass ratio of 5:5 and 4:6 was maintained within 5, and the slight color change was difficult to detect with the naked eye. However, the color difference of the film with a CS / PVA mass ratio of 8:2 and 7:3 exceeded 5, and the color difference was visible to the naked eye. After 2 hours, the pH value of milk dropped from the initial (6.785±0.001) to (5.726±0.002), and the color difference of the four groups of films exceeded 5, and the color change was visible to the naked eye. After 3 hours, the color difference of the four groups of films reached 15.85, 24.55, 15.34, and 10.38 respectively. After 4 hours, pH < 4.5, indicating that the milk has deteriorated. At this time, the color difference of the four groups of films reached 21.48, 28.93, 17.08, and 13.21 respectively, and there was an absolute difference in the color of the four groups of films.

[0070] Figure 6 The correlation between the color difference ∆E of the composite film and the pH value is shown. The determination coefficient (R 2 ) are 0.85449, 0.78075, 0.86544 and 0.91206 respectively. This shows that during the deterioration of milk, there is a correlation between the color difference ∆E of the four CS / PVA / CUR smart films and the pH value of milk. This result also confirms the effectiveness of the smart packaging and can be used for real-time monitoring of milk freshness.

Claims

1. A method for preparing a degradable intelligent food packaging film, characterized in that: The following steps are involved: 1) Dissolve CS in glacial acetic acid solution, heat, stir and condense under reflux to obtain a CS solution; 2) Add PVA to deionized water, heat, stir and condense under reflux to obtain a PVA solution; 3) mixing the CS solution and the PVA solution to obtain a mixed solution; 4) Add glycerol and CUR to the mixture in step 3), keep stirring in a water bath, then cool naturally to room temperature and let stand to eliminate any bubbles that may exist; 5) Cast the mixed solution in step 4) in a culture dish and place it in an oven. After the film is dry, take it out and peel it off.

2. The method for preparing a degradable intelligent food packaging film according to claim 1, characterized in that: In step 1), the dosage ratio of CS to glacial acetic acid solution is 10-30 g / 100 mL, the volume fraction of glacial acetic acid solution is 2%-10%, and the heating temperature is 80-100°C.

3. The method for preparing a degradable intelligent food packaging film according to claim 1, characterized in that: In step 2), the dosage ratio of PVA to deionized water is 10-30 g / 100 mL, and the heating temperature is 80-100° C.

4. The method for preparing a degradable intelligent food packaging film according to claim 1, characterized in that: In step 3), the volume ratio of the CS solution to the PVA solution is 4:1 to 2:

3.

5. The method for preparing a degradable intelligent food packaging film according to claim 1, characterized in that: In step 4), the amount of glycerol added is 30% to 60% of the mass of the solute in the mixed solution.

6. The method for preparing a degradable intelligent food packaging film according to claim 1, characterized in that: In step 4), the amount of CUR added is 1% to 10% of the mass of the solute in the mixed solution.

7. The method for preparing a degradable intelligent food packaging film according to claim 1, characterized in that: In step 4), the water bath temperature is 50-80°C.

8. The method for preparing a degradable intelligent food packaging film according to claim 1, characterized in that: In step 5), the temperature of the oven is 40-70°C.

9. A biodegradable smart food packaging film, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.

10. The use of a degradable smart food packaging film according to claim 9, characterized in that: Used in food packaging films and to monitor the freshness of food.